Nepali Street Drama for Transformation - Kanchhi Maharjan (Interdisciplinary Journal of Management and Social Sciences, 2025)
The drama that began with the beginning of human civilization, adopting various forms, structures and styles, seems to have emerged in the Nepali drama tradition in the thirties. The first street drama, Hami Basant Chodhir, was presented by Pronaam on Bhadra 20, 2039, written and directed by Ashesh Malla, at the open square of Tribhuvan University. Street drama, which emerged in the wake of the street poetry revolution that began to achieve freedom of speech that was completely banned in the Panchayat system, is also seen to have advanced the drama with the aim of transformation. The then administration seems to be afraid of the power of transformation in street drama. As a result, they are seen to have created many problems during the censoring and staging of the drama. The main problem of this article is to study the transformation brought about by the power of street drama in the social, political and economic fields. In this, the transformation brought about by street drama in the social, political and economic fields is determined by the interpretation and analysis of street drama on the theoretical basis of transformation. In this context, a purposive sampling method has been used to select representative street plays from among the street plays published up to 2080 BS. The main conclusion of this study is that since street plays, which originated from a political background, have been raising their voices for freedom of speech from the very beginning, they have made an important contribution to social, political and economic transformation.